Unveiling Differences in Root Defense Mechanisms Between Tolerant and Susceptible Olive Cultivars to Verticillium dahliae - Cardoni, Martina; Gómez-Lama Cabanás, Carmen; Valverde-Corredor, Antonio; Villar, Rafael; Mercado-Blanco, Jesús (Frontiers in Plant Science, 2022)
Verticillium wilt of olive (VWO), caused by the soil-borne vascular pathogen Verticillium dahliae is one of the most devastating diseases affecting this woody crop. One of the best VWO management measures is the use of tolerant cultivars. Yet, our knowledge about defense mechanisms that operate at root level to explain tolerance to this disease is incomplete. Moreover, most of the approaches so far followed focus on a specific mechanistic level (e.g. genetic, physiological or biochemical) rather than on a holistic/multilevel perspective. In this study, eighteen root functional traits, the time course expression of nine defense-related genes, the root lignin content and the root membrane permeability were evaluated in six olive varieties differing in their level of tolerance/susceptibility to VWO. The aim was to find links between the level of tolerance to VWO and specific root defense mechanisms at structural, genetic, biochemical and physiological levels. Tolerant and susceptible cultivars showed substantial differences in root system architecture and root lignin content. VWO-susceptible cultivars presented roots with higher specific length and area, but lower diameter, and larger number of Forks and Tips compared to tolerant varieties that also showed less branched roots, with higher diameter and basal content of lignin. Interestingly, VWO-tolerant varieties significantly increased their root lignin content and root membrane permeability after inoculation with V. dahliae, outcomes not or barely observed in the susceptible plants. At the genetic level, genes related to defense mechanisms such as cell wall lignin biosynthesis (C4H and CO-MT), production of hydrolytic enzyme able to degrade the fungal cell wall (β-1.3-glucanase) and activation of innate immunity (BAK1 and WRKY5) increased their expression in tolerant cultivars from early moments after inoculation, in contrast to the susceptible ones. These results showed that differences in root system architecture and lignin content may greatly determine olive performance against colonization and invasion by V. dahliae. Moreover, the increase in root membrane permeability in the presence of the pathogen was a typical response of tolerant cultivars. Finally, VWO-tolerant cultivars were able to mount a more intense and rapid defense-related genetic response to respond to the attack by V. dahliae.